(untitled) (Journal of Hama University, 2023)
The study was conducted on 12 lambs of Awassi sheep, with an average weight of 26.5 kg, with an average age of 3 months, within a closed breeding system pen divided into two sections with fixed walls. The experiment lasted 110 days. The lambs were randomly distributed into two equal groups. The lambs were fed a standardized concentrated diet for 110 days with a protein content of 17.11%. The difference between the two experiment groups was only in the full feed, where the first group was given hay as a full feed, while the second group was given dried mallow sticks with a ratio of 83 % as a filler feed, in order to know the nutritional value of the mallow sticks and the possibility of using it as a cheap (economically feasible) filler feed alternative for Awassi lambs. The results of the analysis of samples of hay and dried mallow sticks showed that 83% of dried mallow sticks were superior in crude protein content of 7.6% and metabolic energy 2200 kWh/kg compared to straw in which the percentage of crude protein was 2.3% and the metabolic energy was 754 kk. /kg. The results also showed a significant increase at the level of P≤0.05 in the average total weight gain of the lambs of the second group (which ate dried mallow sticks) 24.25 ±0.80 kg compared with the total weight gain of the lambs of the first group 21.00 ±0.48 kg, and the results also showed a significant increase at the level of P ≤0.05 in the average daily weight gain of lambs of the second group 226.62 ±7.46 g compared with the average daily weight gain of lambs of the first group 196.26 ±4.52 g The results indicated that the nutritional value of the mallow sticks outweighed the nutritional value of the straw and that it was possible to use the dried mallow sticks as a filler feed with less material cost (economic feasibility) and educational results (weight gain).